Designing, building, measuring, and testing a constant equivalent fall height terrain park jump - Petrone, N.; Cognolato, M.; McNeil, J. A.; Hubbard, M. (Sports Engineering, 2017)
Previous work has presented both a theoretical foundation for designing terrain park jumps that control landing impact and computer software to accomplish this task. US ski resorts have been reluctant to adopt this more engineered approach to jump design, in part due to questions of feasibility. The present study demonstrates this feasibility. It describes the design, construction, measurement, and experimental testing of such a jump. It improves on the previous efforts with more complete instrumentation, a larger range of jump distances, and a new method for combining jumper- and board-mounted accelerometer data to estimate equivalent fall height, a measure of impact severity. It unequivocally demonstrates the efficacy of the engineering design approach, namely that it is possible and practical to design and build free style terrain park jumps with landing surface shapes that control for landing impact as predicted by the theory.